FACTORS AFFECTING THE NURSING STUDENTS’ ACADEMIC AND CLINICAL PERFORMANCE AND ATTRITION - BANO , S; PARVEEN , T; NAZAR , K (Biological and Clinical Sciences Research Journal, 2023)
Academic performance is the prerequisite of clinical performance in nursing programs which are affected by various factors such as anxiety, lack of supervision, lack of facilities, and many more, resulting in attrition by many students. To evaluate the factors which affect the academic and clinical performance of nursing students in tertiary care institutes along with attrition. After getting REC approval, this study was conducted at the College of Nursing Nishtar Medical University Multan from December 02, 2022, to May 01, 2023. Both genders, ranging from 17-26 years of age, were included in this study. Those who refused to participate were not included. A self-structured questionnaire was formulated, and two field experts checked validity and reliability. Demographic data were depicted in frequencies (%ages), mean, and standard deviation. Association among various factors affecting academic and clinical performance and sociodemographic was checked using chai square in SPSS ver.21. The significance level was <0.05. The mean & SD of age in this study was 21.32+2.57. The association among factors and socio-demographic characteristics demonstrated the effect of these variables on the clinical and academic performance of nursing students, along with the attrition of their degrees. It was concluded that socio-demographic characteristics and attrition affect nursing students’ academic and clinical performance.